PERAN MODAL SOSIAL DALAM PEMBERDAYAAN EKONOMI MASYARAKAT (Studi Kasus Kelompok Usaha Gula Semut di Desa Hargowilis, Kecamatan Kokap, Kabupaten Kulonprogo) - Ratna Dewi Suningsih (EKPI 15 UMY 098, 2015)
*98 This study aims to determine the role of social capital in economic empowerment. Subjects in this study were members of the Group of gula semut from each group in the village Hargowilis, Kokap, Kulon Progo Regency. In this study a sample of 100 respondents were selected using purposive sampling method. The analysis tool used was SPSS 15. Based on the analysis that has been done shows that the role of social capital (trust, social networks, and norms) are jointly and individually significant or significantly different. Trust, social networks and norms are mutually influence each other. If all three of these aspects go hand in hand and are applied in the economic empowerment of the community, the empowerment will be able to increase the empowerment of individuals who apply.